For the Sake of the Light : New and Selected Poems - Sexton, Tom, 1940- (Book collections on Project MUSE., 2009)
This collection of new and selected poems by the former poet laureate of Alaska, Tom Sexton, opens a door on the essence of life in Alaska and Maine. Sexton divides his year between the two states, and he captures here the small but powerful sensual details of day-to-day life in these contrasting, yet similar, environs. His carefully crafted verse distills the birch and aspen, lynx and ptarmigan, and the snow on high peaks. Through his poems we thrill to experience encounters with the wild, the seasons, and the sublime landscape. "His language is clear, without tricks or fancy moves, yet h.